Comparison of MALDI-TOF MS, gene sequencing and the Vitek 2 for identification of seventy-three clinical isolates of enteropathogens - Deng, Jiankai (Pioneer Bioscience Publishing Company, 2014)
OBJECTIVE: This study was performed to evaluate the analytical and practical performance of the matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) compared to the sequencing method and the Vitek 2 system for identiﬁcation of enteropathogens in the clinical microbiology laboratory. METHODS: Ten type strains and 73 clinical isolates of enteropathogens representing eight genera were analyzed by MALDI-TOF MS. All isolates were also characterized by gene sequencing allowing interpretation of the results from MALDI-TOF MS. In addition, MALDI-TOF MS was compared with the Vitek 2 system for the identiﬁcation of ten isolates of Aeromonas and six of Salmonella. RESULTS: As previously known, identification between Shigella and Escherichia coli is not possible to distinguish. MALDI-TOF MS produced the correct identifications for all other type strains and clinical isolates to the genus level. Fifteen Campylobacter jejuni, six Campylobacter coli, three Plesiomonas shigelloides, three Yersinia enterocolitica, two Clostridium difficile, one Vibrio parahaemolyticus, one Vibrio fluvialis, and one Vibrio cholera were all correctly identiﬁed to the species level. Genus and species identifications of ten Aeromonas and six Salmonella isolates by MALDI-TOF MS were consistent with those by the Vitek 2, but with much less cost and about ten times faster. CONCLUSIONS: This study demonstrates that MALDI-TOF MS is a powerful tool for fast, accurate and low-cost identiﬁcation of enteropathogens in the clinical microbiology laboratory.